The Spectrum of Spitz Melanocytic Lesions: From Morphologic Diagnosis to Molecular Classification - Cheng, Tiffany W.; Ahern, Madeline C.; Giubellino, Alessio (Frontiers in Oncology, 2022)
Spitz tumors represent a distinct subtype of melanocytic lesions with characteristic histopathologic features, some of which are overlapping with melanoma. More common in the pediatric and younger population, they can be clinically suspected by recognizing specific patterns on dermatoscopic examination, and several subtypes have been described. We now classify these lesions into benign Spitz nevi, intermediate lesions identified as “atypical Spitz tumors” (or Spitz melanocytoma) and malignant Spitz melanoma. More recently a large body of work has uncovered the molecular underpinning of Spitz tumors, including mutations in the HRAS gene and several gene fusions involving several protein kinases. Here we present an overarching view of our current knowledge and understanding of Spitz tumors, detailing clinical, histopathological and molecular features characteristic of these lesions.